A reação de Diels-Alder entre p-Benzoquinonas 1,3-Pentadienos-1-Substituídos - Finelli, Fernanda Gadini (2004)
In this dissertation, studies are described on the cycloaddition of 1-silyloxypentadiene- 1,3 and 1-acylamino-pentadiene-1,3 with alkylated para-benzoquinones. The first methodology involves cycloaddition reactions of dienes 51, 115 and 116, under catalysis and thermolysis conditions, with para-benzoquinones 37, 42 and 43.The second methodology involves the preparation of the diene in situ from the α,β-unsaturated aldehyde (80) and the amide (81) in the presence of the p-benzoquinones 37, 42 and 43.Theoretical calculations have been carried out on the frontier orbital energies, and the coefficients of the dienes and dienophiles employed in this work, and then compared with the experimental results. Cycloadduct 52 has been studied chemically with the objective of attaining the functionality of common eudesmane sesquiterpenes.